2015
DOI: 10.1007/s00125-015-3673-x
|View full text |Cite
|
Sign up to set email alerts
|

MAFB as a novel regulator of human adipose tissue inflammation

Abstract: Aims/hypothesis Dysregulated expression of metabolic and inflammatory genes is a prominent consequence of obesity causing insulin resistance and type 2 diabetes. Finding causative factors is essential to understanding progression of these pathologies and discovering new therapeutic targets. The transcription factor V-maf musculoaponeurotic fibrosarcoma oncogene homologue B (MAFB) is highly expressed in human white adipose tissue (WAT). However, its role in the regulation of WAT function is elusive. We aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Enhanced hyper-methylation of these genes by post-exercise milk product intake may suppress MAP kinase signaling, as well as NF-κB signaling pathways [5356]. On the other hand, enhanced hypo-methylation of MYC by post-exercise milk product intake (Fig 6) may be a reaction to the aforementioned hyper-methylation to balance the inflammatory response [57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced hyper-methylation of these genes by post-exercise milk product intake may suppress MAP kinase signaling, as well as NF-κB signaling pathways [5356]. On the other hand, enhanced hypo-methylation of MYC by post-exercise milk product intake (Fig 6) may be a reaction to the aforementioned hyper-methylation to balance the inflammatory response [57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that tumor necrosis factor (TNF) α, a proinflammatory cytokine, increased MafB expression in human monocytic cells and primary adipocytes [7,9,13]. Besides, Borrelli et al identified MafB as a direct transcriptional target of C/EBPδ in human primary keratinocytes by ChIP on chip assays [14].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, MafB was shown to form heterodimers with v-Maf and Fos through its zipper structure and induced transformation of chicken embryo fibroblasts in vitro [5]. Subsequent studies found that MafB played an important role in the regulation of pancreatic alpha cell, beta cell, osteoclast, macrophage and adipocyte differentiation [6][7][8][9][10]. Besides, MafB was viewed as a highly sensitive and specific marker for poor prognosis in multiple myeloma patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed human MAFB and AIM were coexpressed in atherosclerosis lesion of patient [9]. In addition, a recent study showed that human MAFB is expressed in ATMs and MAFB expression correlates negatively with lipogenesis and lipolysis in human adipocytes [28]. These evidence suggest that MAFB may regulate AIM expression in human ATMs because AIM also inhibits fatty acid synthase activity of adipocyte [16].…”
Section: Discussionmentioning
confidence: 88%